Curricular design elements for the training of master students in the field of physical education and sport for management research activities - Volcu Gheorghe; Volcu Irina (Editura Univeristatii "Stefan cel Mare" din Suceava, 2022)
It contains references to the approached topic, the purpose of the paper, the used methods, the main results and the conclusions. This article addresses the issue of professional training of master students of physical education and sport for managerial research. In this context, curriculum design is proposed for the above-mentioned issue. With a relative periodicity, in all educational systems the curriculum goes through a process of updating or reform, depending on the nature and extent of the changes pursued. The designed curriculum substantiates and guides the work of the teacher, facilitates the creative approach of the projective approaches and of the actual realization of the educational process.